Mitochondrially targeted tamoxifen as anticancer therapy: case series of patients with renal cell carcinoma treated in a phase I/Ib clinical trial - Bielcikova, Zuzana; Werner, Lukas; Stursa, Jan; Cerny, Vladimir; Krizova, Ludmila; Spacek, Jan; Hlousek, Stanislav; Vocka, Michal; Bartosova, Olga; Pesta, Michal; Kolostova, Katarina; Klezl, Petr; et al. (Therapeutic advances in medical oncology, 2023)
Mitochondrially targeted anticancer drugs (mitocans) that disrupt the energy-producing systems of cancer are emerging as new potential therapeutics. Mitochondrially targeted tamoxifen (MitoTam), an inhibitor of mitochondrial respiration respiratory complex I, is a first-in-class mitocan that was tested in the phase I/Ib MitoTam-01 trial of patients with metastatic cancer. MitoTam exhibited a manageable safety profile and efficacy; among 37% (14/38) of responders, the efficacy was greatest in patients with metastatic renal cell carcinoma (RCC) with a clinical benefit rate of 83% (5/6) of patients. This can be explained by the preferential accumulation of MitoTam in the kidney tissue in preclinical studies. Here we report the mechanism of action and safety profile of MitoTam in a case series of RCC patients. All six patients were males with a median age of 69 years, who had previously received at least three lines of palliative systemic therapy and suffered progressive disease before starting MitoTam. We recorded stable disease in four, partial response in one, and progressive disease (PD) in one patient. The histological subtype matched clear cell RCC (ccRCC) in the five responders and claro-cellular carcinoma with sarcomatoid features in the non-responder. The number of circulating tumor cells (CTCs) was evaluated longitudinally to monitor disease dynamics. Beside the decreased number of CTCs after MitoTam administration, we observed a significant decrease of the mitochondrial network mass in enriched CTCs. Two patients had long-term clinical responses to MitoTam, of 50 and 36 weeks. Both patients discontinued treatment due to adverse events, not PD. Two patients who completed the trial in November 2019 and May 2020 are still alive without subsequent anticancer therapy. The toxicity of MitoTam increased with the dosage but was manageable. The efficacy of MitoTam in pretreated ccRCC patients is linked to the novel mechanism of action of this first-in-class mitochondrially targeted drug.
Keywords: mechanism of action; case series; safety; efficacy; mitochondria; MitoTam; phase I/Ib trial; mitocans; mitochondrially targeted tamoxifen; renal cell carcinoma